Genome‐wide characterization of nuclear factor Y transcription factors in Fagopyrum tataricum. Issue 2 (23rd March 2022) - Zhang, Ling; Yung, Wai‐Shing; Sun, Wei; Li, Man‐Wah; Huang, Mingkun
Abstract: The nuclear factor Y (NF‐Y) is an important transcription factor family that regulates plant developmental processes and abiotic stress responses. Currently, genome‐wide studies of the NF‐Y family are limited in Fagopyrum tataricum, an important economic crop. Based on the released genome assembly, we predicted a total of 38 NF‐Y encoding genes ( FtNF‐Ys ), including 12 FtNF‐YAs, 18 FtNF‐YBs, and eight FtNF‐YCs subunits, in F. tataricum . Phylogenetic tree and sequence alignments showed that FtNF‐Ys were conserved between F. tataricum and other species. Tissue expressions and network analyses suggested that FtNF‐Ys might be involved in regulating developmental processes in different tissues. Several FtNF‐YAs and FtNF‐Ybs were also potentially involved in light response. In addition, FtNF‐YC‐like1 and FtNF‐YC‐like2 partially rescued the late flowering phenotype in nf‐yc1 nf‐yc3 nf‐yc4 nf‐yc9 ( ycQ ) mutant in Arabidopsis thaliana, supporting a conserved role of FtNF‐Ys in regulating developmental processes. Together, the genomic information provides a comprehensive understanding of the NF‐Y transcription factors in F. tataricum, which will be useful for further investigation of their functions in F. tataricum .